The Placental Microbiota Is Altered among Subjects with Gestational Diabetes Mellitus: A Pilot Study - Jia Zheng; Xinhua Xiao; Qian Zhang; Lili Mao; Miao Yu; Jianping Xu; Tong Wang (Frontiers in Physiology, 2017)
Gestational diabetes mellitus (GDM) has significant implications for the future health of the mother and child. However, the associations between human placental microbiota and GDM are poorly understood. We aimed to profile the placental microbiota of GDM and further define whether or not certain placental microbiota taxon correlates with specific clinical characteristics. Placenta were collected from GDM women and women with normal pregnancies (n = 10, in each group) consecutively recruited at Peking Union Medical College Hospital. The anthropometric parameters of mother and infant, and cord blood hormones, including insulin, leptin and insulin-like growth factor-1 (IGF-1) were measured. Bacterial genomic DNA was isolated using magnetic beads and the human placental microbiota was analyzed using the Illumina MiSeq Sequencing System based on the V3-V4 hypervariable regions of the 16S rRNA gene. It showed there was no statistical difference in the clinical characteristics of mothers and infants, such as BMI at the beginning of pregnancy and gestational weight gain (GWG), birth weight, and cord blood hormones, including insulin, leptin and IGF-1. We found that the placental microbiota is composed of four dominant phyla from Proteobacteria (the most abundant), Bacteroidetes, Actinobacteria and Firmicutes, with the proportion of Proteobacteria increased, and Bacteroidetes and Firmicutes were decreased of women with GDM. Further analyses suggested that bacterial taxonomic composition of placentas from the phylum level down to the bacteria level, differed significantly between women with GDM and non-GDM women with normal pregnancies. Regression analysis showed a cluster of key operational taxonomic units (OTUs), phyla and genera were significantly correlated with GWG during pregnancy of mothers, and cord blood insulin, IGF-1 and leptin concentrations. In conclusion, our novel study showed that a distinct placental microbiota profile is present in GDM, and is associated with clinical characteristics of mothers and infants. This study contributes to the theoretical foundation on the potential relationship between placental microbiota and GDM.